Peningkatan Pemahaman Konsep Bangun Ruang Sisi Datar melalui Pendekatan Konkret dalam Pembelajaran Matematika - Sinaga , D Yuliana; Hutagalung, Nahya Azrina Zahara; Purba, Agnes Cecilia Yohana; Simatupang, Nadia Anastasia; Harianja, Zenni Gonlia; Sinaga, Maria Virginia; Gultom, Elena (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study explores the effectiveness of a concrete approach in mathematics education, specifically focusing on flat-sided spatial figures at SD Inpres No 097320 Serapuh. A qualitative methodology involving classroom observations and in-depth interviews with teachers and students was employed. The findings reveal that the use of manipulatives enhances students' understanding of spatial figures and engages them more actively in the learning process. Despite logistical challenges, such as limited availability of manipulatives, this study supports the adoption of a concrete approach to improve the effectiveness of mathematics education. Recommendations include increasing access to manipulatives and integrating educational technology to enrich students' learning experiences.